Vídeo, mediação e pandemia: um estudo a partir da utilização do vídeo em sala de aula - Brudzinski, Marcus Vinicius (2023)
The objective of this research is to highlight teachers’ perceptions about the development and use of video in the classroom. This language has been appropriated as a didactic resource by teachers, who became producers of videos with specific content between 2020 and 2021, the period of the Covid-19 pandemic. In teaching practice, in order to resolve the gap between teacher and student, the video must be thought of in the instrumental matrix (as a tool), but also in the relational matrix (as language), that is, criteria and strategies for choosing of the best tool option to convey the language, bearing in mind the diversity in the production of each teaching/lesson plan. To methodologically make this study feasible, a bibliographical review was carried out on theoretical axes such as the language of video, image and device (Arlindo Machado, Vilém Flusser, Jacques Aumont, Philippe Dubois, Walter Benjamin), mediation (Jesús Martín-Barbero) and technological determinism (Alberto Cupani, Andrew Feenberg, Langdon Winner), followed by the application and analysis of a questionnaire and interviews with higher education professors from a private university who learned and used the language of the video in part of their classes during the pandemic. As a result, it was found that technology alone was not responsible for the effectiveness of content transmission, without the teacher’s decision on how to do it. With this research and its results, teachers/producers are given a voice in their negotiations with devices and languages, encouraging others to continue in the effort to promote learning.